THE POSITION OF FAMILIES IN THE NETHERLANDS (Годишен зборник на Филозофски факултет - Скопје, 2021)
This paper analyzes the situation of families in the Netherlands. Marriage and relationships are analyzed, i.e., the manner of concluding and breaking up, the necessary conditions, and the like. Parenting, the rights, and obligations that arise, as well as the general family structure of families in the Netherlands. To get a broader picture of the families in this country, a review of several indicators was made and the statistical indicators for marriages, divorces and live births from 1950 to 2017 were compared. The main assumption is that a liberal society provides better conditions for the development and advancement of families.